On the evolution of the accuracy, within-game consistency, and geometry of the called strike zone in Major League Baseball from 2008-2023 - Post, R.; Tang, J.; Zimmerman, D. L. (Journal of Sports Analytics, 2025)
The accuracy and consistency with which home plate umpires call pitches can play a significant role in the outcomes of Major League Baseball (MLB) games. Here, we investigate trends in called pitch accuracy (percentage of pitches called correctly) and within-game consistency for all regular season Major League Baseball games from 2008-2023, and we map the locations of these pitches to quantify how well the geometry of the strike zone established by the decisions made by umpires (called strike zone, CSZ) aligns with that of the rule-book strike zone (RBSZ) in each season. Our results show that there was steady improvement in both accuracy (from less than 86% to almost 92%) and within-game consistency of the CSZ, although the rate of improvement slowed in the last few years of the time period. By 2023 the CSZ's geometry aligned with that of the RBSZ in every respect except its size, which was still about 10% too large. The implications of these levels and trends in umpire performance metrics for the forthcoming implementation of an automated system for calling balls and strikes in MLB are discussed.